Morphological studies of randomized dispersion magnetite nanoclusters coated with silica - Huang, N.M.; Haw, C.Y.; Chia, C.H.; Zakaria, S.; Mohamed, F.; Radiman, S.; Teh, C.H.; Khiew, P.S.; Chiu, W.S. (2011)
In this study, we report a simple way to produce randomized dispersion magnetite nanoclusters coated with silica (RDMNS) via StÃ¶ber process with minor modifications. The morphology of silica coated magnetite nanoclusters was emphasized by studying various reaction parameters including alcohols with different polarities as co-solvents, concentration of alcohol-water, concentration of alkaline catalyst (ammonia), and concentration of TEOS monomer. The results of transmission electron microscope (TEM) showed that the sizes and morphological behaviour of the magnetite nanoclusters vary accordingly with the different reaction parameters investigated. The results showed that ethanol would be the best candidate as co-solvent in the preparation of randomized dispersion magnetite nanoclusters. Besides, the optimum alcohol-water ratio has been determined to be 70-30 v/v as this concentration range could render desired shape of randomized dispersion magnetite nanoclusters. The volume of ammonia (NH 3) catalyst in the reaction media also strongly governs the formation of silica coated magnetite nanoclusters in a desired shape. Apart from that, the addition of TEOS monomer into the reaction media has to be well-controlled as the excess amount of monomer added might affect the thickness of the silica layer that is coated on the magnetite nanoparticles. Prior to silica coating, the bare magnetite nanoparticles were first treated with trisodium citrate (0.5 M) to enhance the particles' dispersibility. Improvement in the size distribution and dispersibility of the magnetite nanoparticles after the citrate treatment has been examined using TEM. The XRD results show that the magnetite samples retained good crystallinity although they have been surface-modified with citrate group and silica. The Fourier transform infrared (FT-IR) and thermogravimetric analysis (TGA) prove that the magnetite nanoparticles have been successfully coated with citrate and silica. The superparamagnetic behaviour of the magnetite samples was confirmed by VSM. The produced silica coated magnetite nanoclusters possess great potential to be applied in bio-medical research and clinical diagnosis application. Â© 2010 Elsevier Ltd and Techna Group S.r.l.